Rapid determination of total metals: synergic effect of ultrasound energy and ionic liquids on the digestion of sediment samples - Alvarez, Silvana María (2021)
Purpose: The aim of this study was to develop a new and rapid sample digestion procedure for metal extraction using ultrasonic energy together with a combination of an ionic liquid and mineral acids as extractants. Methods: A fixed mass of sediment (about 0.50 g) was extracted with a combination of low volumes of NaHCO3, HCl, HNO3, HF and the ionic liquid Bmim[BF4]. Afterwards, the mixture was sonicated for 20 min. After neutralizing the hydrofluoric acid excess, the extracts were filtered and measured by ICP OES where Cd, Cr, Cu, Ni, Pb and Zn were determined. Results: The recoveries in certified reference materials ranged from 92 to 102% for LGC-6137, from 88 to 98% for IAEA SL-1 and from 81 to 98% for MURST-ISS-A1, with a good precision (relative standard deviation (RSD) < 10.0% for all the certified reference materials). The new digestion procedure was successfully applied to the determination of metals in estuarine sediment samples, with a satisfactory precision (RSD < 9.5%). The results showed no significant statistical differences compared to those obtained by the conventional digestion procedure (with an α-error of 0.05). Conclusion: This approach has led to satisfactory results in the determination of the total metal concentrations for most of the elements studied using shorter analysis times than the conventional procedure, and small volumes of hydrofluoric acid. The new pretreatment method made it possible to satisfactorily assess the total metal concentrations in estuarine sediments.